Metodologia de apoio a seleção de sistemas construtivos mais sustentáveis para habitações rurais no contexto brasileiro - Barboza, Christian Souza (2019)
The lack of decent housing for people living in the countryside is one of the main factors of social vulnerability, with rural housing shortage reaching 783 thousand in Brazil. The construction industry is of great importance for the mitigation of this situation, with significant participation in the process of social, economic and environmental transformation. The industry now starts to reframe itself, incorporating concepts of sustainability in its construction processes. Since the early 2000s, several methodologies for the evaluation of sustainable performance of buildings have been proposed. However, the vast majority of these methodologies is focused on the assessment of the impacts of the urban environment of large centers on the surroundings. In order to evaluate the contribution to promote sustainability of buildings in rural environments by comparing the performance of traditional and alternative building systems, the present work proposes, using interest group surveys and the analysis of other evaluation methodologies and of application context, the creation of a decision aid method for choosing more sustainable building systems, which are aimed for rural housing of social interest. The proposed method is based on modeling built from Analytic Hierarchy Process (AHP), using the performance of the constructive system in four proposed aspects (“Ecological and Environmental”, “Social, Historical and Cultural”, “Economic and Financial” and “Technical and Performance”) as selection criteria. Due to the complexity and number of variables, a computational tool was built, using the Python programming language, to automate the processing of data. A case study was carried out to assess the model, in Assentamento Itamarati, located in the rural area of Ponta Porã-MS, Brazil. In this study, four wall solutions were compared (ceramic blocks, concrete blocks, compact soil-cement blocks and mechanically pressed compressed soil blocks). The soil-based systems had the best performance, of 29.00% and 26.30% for soil-cement blocks and compressed soil blocks, respectively, compared to the industrialized ceramic (22.63%) and concrete (22.07%) blocks. It is noticeable, from the results, that the proposed methodology presents itself as a viable solution for the implementation of constructive practices that contribute to the promotion of sustainability of buildings, customized to the reality of the countryside.